Pemanfaatan Media Papan Pintar Angka (PAPIKA) untuk Meningkatkan Kemampuan Logika Matematika Anak Usia 4-5 Tahun di TK Permata Bunda Sungailiat - Lestari, Sri (ICEJ : Islamic Childhood Education Journal, 2024)
The problem of this research is to find out more about the process carried out by teachers in implementing the smart number board (Papika) media to improve the mathematical logic skills of children aged 4-5 years at Permata Bunda Sungailiat Kindergarten, in this case the children are not yet able to order numbers 1- 10, the child still goes back and forth in saying certain numbers. This research uses descriptive qualitative research at Permata Bunda Sungailiat Kindergarten. The object of the research is the application of smart number board media to improve children's logical abilities. The research subjects were the principal, class teacher, and 10 children aged 4-5 years at Permata Bunda Sungailiat Kindergarten. data sources obtained from primary and secondary data. Data collection techniques used in research are interviews, observation and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the research show that the application of Papika to improve mathematical logic skills in Permata Bunda Kindergarten, before starting learning the teacher prepares a Daily Learning Implementation Plan (RPPH). The results of the research show that in improving children's mathematical logic skills through the use of Papika media, before starting the teacher invites children to form groups before playing, the teacher explains the rules for playing Papika media, children play Papika media. And the assessment of children's achievements is that children are able to say numbers 1-10, children are able to mix numbers with number symbols, children are able to recognize flat geometric shapes, children are able to recognize various colors.